1995
DOI: 10.1055/s-0038-1653722
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel and Rapid Whole Blood Assay for D-Dimer in Patients with Clinically Suspected Pulmonary Embolism

Abstract: SummaryStudy Objective: To determine the clinical utility of a novel whole blood assay for D-dimer (SimpliRED™) in patients with clinically suspected pulmonary embolism (PE).Design: Prospective cohort.Patients: Eighty-six consecutive patients with clinically suspected PE.Intervention: All patients had the SimpliRED D-dimer assay performed and underwent ventilation/perfusion (V/Q) lung scanning and bilateral impedance plethysmography (IPG); pulmonary angiography was performed in two patients. Patients were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 17 publications
3
59
1
1
Order By: Relevance
“…This SimpliRED method had a sensitivity of 93% for proximal DVT, but only 70% for distal DVT. Other investigators also reported high sensitivity and negative predictive value for this rapid whole blood assay in suspected pulmonary embolism 11 and suspected DVT. 12 In our study, selection bias may have resulted from excluding patients with symptoms exceeding 7 days' duration; however, the time lag between the thrombotic event and diagnostic procedures may result in a false-negative D-dimer result.…”
Section: Discussionmentioning
confidence: 81%
“…This SimpliRED method had a sensitivity of 93% for proximal DVT, but only 70% for distal DVT. Other investigators also reported high sensitivity and negative predictive value for this rapid whole blood assay in suspected pulmonary embolism 11 and suspected DVT. 12 In our study, selection bias may have resulted from excluding patients with symptoms exceeding 7 days' duration; however, the time lag between the thrombotic event and diagnostic procedures may result in a false-negative D-dimer result.…”
Section: Discussionmentioning
confidence: 81%
“…The diagnostic performance of the new test is identical to that of classical ELISA assays. Novel whole-blood bedside latex assays for D-dimer seem equally promising (30,31), but the experience with these tests is still limited, and the problem of interobserver variability inherent to the latex technique was not addressed in the studies in which it showed promise. Moreover, the latex assays do not provide quantitative results.…”
Section: Discussionmentioning
confidence: 99%
“…Semiquantitative Latex agglutination assays are rapid, but their sensitivity is too low for them to be used as an exclusion test. New rapid D-Dimer assays have recently been developed, and pilot studies have proved promising; however, because of the limited number of patients tested, large confidence intervals of their diagnostic performances have been reported (18,19).…”
mentioning
confidence: 99%